Taking sides clashing views on controversial issues in cultural anthropology - Welsch, Robert Louis 1950-.; Endicott, Kirk M. (Guilford, Ct. McGraw-Hill/Dushkin, 2003)
This [text] is a debate-style reader designed to introduce students to controversies in cultural anthropology. The readings, which represent the arguments of leading anthropologists and educators, reflect a variety of viewpoints, and have been selected for their liveliness and substance, their relevance to the topics included in college-level study of cultural anthropology, and because of their value in a debate framework.--Back cover.
Theoretical orientations: Should cultural anthropology model itself on the natural sciences?; Do native peoples today invent their traditions?; Do museums misrepresent ethnic communities around the world? -- Some specific issues in cultural anthropology: Was Margaret Mead's fieldwork on Samoan adolescents fundamentally flawed?; Does language determine how we think?; Are San Hunter-Gatherers basically pastoralists who have lost their herds?; Do Hunter-Gatherers need supplemental food sources to live in tropical rain forests?; Do sexuality Egalitarian societies exit?; Is it natural for adopted children to want to find out about their birth parents?; Has the Islamic revolution in Iran subjugated women?; Are Yanomami violence and warfare natural human efforts to maximize reproductive fitness?; Do some illnesses exit only among members of a particular culture? -- Ethics in cultural anthropology: Did Napoleon Chagnon and other researchers harm the Yanomami Indians of Venezuela?; Does it matter if Novel Peace Prize Winner Rigoberta Menchu's memoir contains inaccuracies?; Should anthropologists work to eliminate the practice of female circumcision?; Do anthropologists have a moral responsibility to defend the interests of "Less Advantaged" communities?
Includes bibliographical references and index.
Keywords: Ethnology